Peran UNHCR dalam Menangani Climate Refugees India di Asia Selatan - Hasanah, Nur Alfina; Al Farauqi, Mohamad Dziqie Aulia; Amin, Khoirul; Rukmana, Gilang Mukti; Tyas, Intan Kinanthi Damarin; Paramitha, Devi Indah (Departemen Hubungan Internasional, Fakultas Ilmu Sosial dan Ilmu Politik, Universitas Padjadjaran, 2023)
Abstract This study describes the dilemma and the role of UNHCR in dealing with the problem of climate refugees in India. India is the host country for most refugees in South Asia however it still but has not ratified the 1951 Convention and the 1967 Protocol regarding Refugees status and protocols. South Asia is one of the areas that are very vulnerable to climate change, population density, poverty, and lack of resources for climate change adaptation are the main obstacles for the region, also the geographical condition of South Asia which borders the Himalayas in the north and east, the Indian Ocean in the southern part. These two geographical boundaries are vulnerable to climate change, this study uses the theory of transnational interaction between countries and the theory of intergovernmental organizations (IGOs). This type of research uses descriptive research and uses qualitative analysis techniques. The method used in this research data collection is a literature study. This study has an initial argument, namely the role of UNHCR in India is Refugee Status Determination (RSD) in the form of interviewing asylum seekers and verifying documents for refugee status which then issues certified temporary residence to people who meet the criteria, and assists the voluntary repatriation of refugees by coordinate with relevant countries. By carrying out its duties, UNHCR also collaborates with NGOs in India such as Don Bosco Ashalyan, Young Men Christian Association (YMCA), National Institution for Transforming India (Niti Ayong), and Social Law Information Center (SLIC), Development and Justice Initiative (DAJI). , Save the Children India (SCI), Indian Society of International Law (ISIL).